A Brief Overview of the Relevant Findings From Positive Psychology on Childhood Development: The Concept of Protective Factors and Resilience in Childhood - Rijavec, Majda; Balaž, Barbara (Social and Personality Development in Childhood, 2025)
This chapter focuses on an overview of the contribution of positive psychology’s findings to the body of knowledge about children’s resilience. Firstly, different definitions of resilience are presented, which conclude that resilience is a process consisting of two mutually related conditions - the experience of severe adversity and positive adaptation despite it. Along with adversity, researchers refer to risk factors which are related to higher rates of undesirable developmental outcomes, and could include individual, family and environmental factors. Another inseparable dimension of resilience is positive adaptation which refers to better-than-expected outcomes despite the exposure to the risk factors. It could be assessed as the absence of psychopathological symptoms or as positive behaviors. Besides this, it could be examined as internal or external adaptation or both.Research on positive adaptation revealed that resilience and positive adaptation are context specific. Alongside positive adaptation, there are protective factors which refer to variables that are related to better-than-expected. Secondly, there is presented the contribution of the field of positive psychology to the research on children’s resilience. Positive psychology moved away from the psychopathology perspective to an approach that focusses on strengths and resources which significantly contributed to development in the field of resilience. From this perspective resilience is not merely the absence of symptoms but also includes positive changes. Positive psychology contributed to the research on these positive changes in various areas, including protective factors in resilience and post-traumatic growth. Thirdly, there are presented positive psychology interventions aimed at fostering resilience. The chapter concludes with final remarks about the relationship between children’s resilience and positive psychology.Keywords: adversity, positive adaptation, positive psychology, protective and risk factors, resilience